The influence of transformational and transactional leadership on dyadic trust relationships through perceptions of fairness - P. Krafft; A. S. Engelbrecht; C. C. Theron (SA Journal of Industrial Psychology, 2004)
Leadership and interpersonal trust are critical issues for the survival of organisations. Both aspects have been researched thoroughly, but the role organisational justice might play in this relationship has been largely ignored. The purpose of this study was to investigate the relationship between transformational and transactional leadership and interpersonal trust, and whether organisational justice plays a mediating role. Through LISREL analysis, it was found that interactional justice played a greater role in the relationship between transformational leadership and trust than procedural justice. Distributive justice mediated the relationship between transactional leadership and trust. Opsomming Leierskap en interpersoonlike vertroue is kritieke vraagstukke vir die oorlewing van organisasies. Beide aspekte is reeds deeglik nagevors, maar die rol wat organisatoriese geregtigheid in hierdie verband kan speel, is grootliks nagelaat. Die doel van hierdie studie was om die verband tussen transformasionele en transaksionele leierskap en interpersoonlike vertroue te ondersoek, en of organisatoriese geregtigheid ’n tussenkomende rol speel. Deur middel van LISREL-ontleding is gevind dat interaktiewe geregtigheid ’n groter rol in die verband tussen transformasionele leierskap en vertroue speel as prosedurele geregtigheid. Verdelende geregtigheid dien as tussenkomende veranderlike in die verband tussen transaksionele leierskap en vertroue.